1994
DOI: 10.1159/000126768
|View full text |Cite
|
Sign up to set email alerts
|

Neurokinin B Gene Expression Is Increased in the Arcuate Nucleus of Ovariectomized Rats

Abstract: Hypertrophy and increased gene expression of tachykinin neurons occur in the infundibular (arcuate) nucleus of postmenopausal women. We have hypothesized that the alterations in tachykinin gene expression in the hypothalami of postmenopausal women are secondary to ovarian failure and not due to age per se. In this study, in situ hybridization and computer-assisted microscopy were used to determine whether ovariectomy modulates neurokinin B (NKB), substance P (SP) or proopiomelanocortin (POMC) gene expression i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
90
1
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 110 publications
(106 citation statements)
references
References 33 publications
14
90
1
1
Order By: Relevance
“…www.reproduction-online.org and the ventromedial nucleus (VMN), in keeping with previous reports of SP immunoreactivity in rats, monkeys and humans (Ronnekleiv et al 1984, Yamano et al 1986, Harlan et al 1989, Rance & Young 1991, Tsuruo et al 1991, Rance & Bruce 1994, Borsay et al 2014. Studies using immunohistochemical detection of SP also report a plethora of fibers that innervate the entire length of the ARC and the median eminence (ME) (Hrabovszky et al 2013, Kalil et al 2015, Fergani et al 2016, which appear to surround the capillaries of the hypophyseal portal system indicating that SP may have the ability to act directly on the anterior pituitary (Kalil et al 2015).…”
Section: Distribution Of Sp and Nka In The Hypothalamus And Anatomicasupporting
confidence: 86%
See 1 more Smart Citation
“…www.reproduction-online.org and the ventromedial nucleus (VMN), in keeping with previous reports of SP immunoreactivity in rats, monkeys and humans (Ronnekleiv et al 1984, Yamano et al 1986, Harlan et al 1989, Rance & Young 1991, Tsuruo et al 1991, Rance & Bruce 1994, Borsay et al 2014. Studies using immunohistochemical detection of SP also report a plethora of fibers that innervate the entire length of the ARC and the median eminence (ME) (Hrabovszky et al 2013, Kalil et al 2015, Fergani et al 2016, which appear to surround the capillaries of the hypophyseal portal system indicating that SP may have the ability to act directly on the anterior pituitary (Kalil et al 2015).…”
Section: Distribution Of Sp and Nka In The Hypothalamus And Anatomicasupporting
confidence: 86%
“…This is supported by the anatomical findings that virtually all KNDy neurons express NK3R (Navarro et al 2009, 2011b, Amstalden et al 2010) and >90% express kappa-opioid receptor (KOR; (Weems et al 2016)). Furthermore, KNDy cells are interconnected with NKB fibers within the ARC forming a tightly regulated network (Rance & Bruce 1994, Krajewski et al 2010. Indeed, a growing number of studies in multiple species from our lab and others support the ability of NKB, or the NKB receptor (NK3R) agonist senktide, to increase LH pulses (Grachev et al 2012, Navarro 2013, Goodman et al 2014 (Arisawa et al 1990, Kalra et al 1992, Sahu & Kalra 1992, Noritake et al 2011, de Croft et al 2013 including men (Coiro et al 1992).…”
Section: The Current Model For the Gnrh Pulse Generatormentioning
confidence: 99%
“…Because the decrease in the number of kisspeptin neurons during the non-breeding season is considered to be mainly due to the reduced expression of kisspeptin rather than to apoptosis [30], the very similar ratio of colocalization of kisspeptin and NKB between the breeding [13] and non-breeding seasons suggests that the expression of NKB in the ARC is also suppressed during the non-breeding season and that photoperiodic regulation of the expression occurs in a similar direction and extent between kisspeptin and NKB. In monkeys [30], rodents [9,31] and sheep [32], it has been shown that ovariectomy increases while E2 decreases the expression of NKB in the ARC, as is the case with kisspeptin [5,28]. Moreover, the number of kisspeptin- [33,34] and NKB-positive [34] neurons in the ARC are reduced in a similar manner during lactation in rats.…”
Section: Discussionmentioning
confidence: 90%
“…Secretion of GnRH into portal capillaries stimulates LH secretion from the anterior pituitary gland, which stimulates the secretion of E 2 from the ovaries. E 2 negative feedback reduces serum LH and decreases NKB and kisspeptin mRNA in KNDy neurons (57,58). ERα, the isoform required for estrogen negative feedback (59), is expressed in arcuate KNDy neurons (60) but not GnRH neurons (61).…”
Section: Methodsmentioning
confidence: 99%
“…The MnPO receives information from warm-sensitive, cutaneous thermoreceptors and projects to CNS centers to modulate heatdissipation effectors (24,42). (B) Effects of ovariectomy on serum LH and tail skin vasodilatation: Loss of E 2 after ovariectomy markedly increases NKB and kisspeptin gene expression in KNDy neurons (57,58), increases GnRH secretion into the portal capillaries (63) and LH secretion from the anterior pituitary gland. In the MnPO, at neutral T AMBIENT , Fos is increased in OVX rats, compared with OVX + E 2 rats (37).…”
Section: Methodsmentioning
confidence: 99%